Optimization study of return vent height for an impinging jet ventilation system with exhaust/return-split configuration by TOPSIS method. (15th June 2020) - Ye, Xiao; Kang, Yanming; Yan, Zhenrong; Chen, Bin; Zhong, Ke
Abstract: For impinging jet ventilation (IJV) system, the energy efficiency is believed to be further improved by splitting the return vent from the exhaust device. However, how to properly set the return devices of IJV is unclear when it comes to a comprehensive consideration of the thermal comfort, indoor air quality (IAQ) and energy efficiency. In the present study, numerical simulations are performed to determine the thermal comfort indices (draught comfort (PD) and temperature gradient between the head and ankle levels (Δ T )), IAQ indices (air change efficiency (ACE) and contaminant removal efficiency ( ε )) and energy efficiency index ( η ) for an IJV system with return outlet height ( H ) ranged from the ceiling to the floor level. The technique for order preferences by similarity to an ideal solution (TOPSIS) method is employed to determine the optimal return vent height by considering these performance evaluation indices simultaneously. The results indicate that when the H increases, the values of Δ T and η decrease, while the values of PD, ACE and ε increase. An optimal range of H (1.2–1.5 m above the floor) is recommended for the best overall performance of IJV. Moreover, a comprehensive graph of H is displayed in this paper, which could provide directions for optimizing the positions of exhaust and return devices. Graphical abstract: Image 1 Highlights: Impinging jet ventilation (IJV) with separate exhaust and return devices is studied. Thermal comfort, indoor air quality and energy efficiency are considered together. Short-circuit flow phenomenon of supply cold air might be occurred in the IJV. An optimal return vent height ( H ) range for IJV is achieved by using TOPSIS method.